University Students' Perceptions of Peer Assessment in Oral Presentations - Diego Gudiño; María-Jesús Fer; María-Teresa B; Susana Sánchez-Herrera (MDPI AG, 2024)
Peer assessment has been shown to be useful in a variety of educational contexts, but there is a scarcity of research on how prior experience affects university students' perceptions of this form of assessment. This study evaluates whether experience with peer assessment of oral presentations influences the perceptions and self-efficacy of university students as assessors. In the study, 58 university students completed a comprehensive questionnaire before and after assessing the oral presentations of their peers. The results indicate that prior to the assessment the students reported having limited experience, but they considered this practice beneficial to their learning. Afterwards, they showed a higher degree of agreement regarding their confidence in the ability of their peers to assess both superficial aspects and the content of the presentations. In addition, the experience helped them to feel that their ability to assess their peers was not inferior to that of their classmates. It may therefore be concluded that practice and training in peer assessment improve the students' perception of this form of assessment, although a single session is insufficient. Consistent and extended training is crucial to achieve a substantial impact.